Perspektif Tenaga Kesehatan Terhadap Kualitas Pelayanan Puskesmas Pasca Akreditasi - Nikmah, Faizatun; Sujoso, Anita Dewi Prahastuti; Utami, Wiwien Sugih (Puslitbang Sinergis Asa Professional, 2024)
Primary Healthcare Centers use accreditation as reference for improving health services quality. Health workers are the main component in providing health services at Primary Healthcare Center, but they have not felt the impact of accreditation on service quality. The study intend to figure out the perspective of health workers on the quality of health services in 44 Primary Healthcare Centers in Jember Regency after the implementation of accreditation. The type of study used is quantitative analytic with 330 health worker respondents. Interview was used to collect data while SEM-PLS was used to analyze data. Selection of study samples using multistage random sampling technique. Multistage random sampling is group sampling, where for each group selected as a sample, sample elements from each group are selected again. First, determine the primary healthcare centers to be studied from the 50 primary healthcare centers using the Slovin formula. The calculation results obtained were for 44 primary healthcare centers randomly. The second step was to select a sample of health workers from 1,866 people based on the sample size formula using the Slovin formula, resulting in 330 health workers. This study resulted that that leadership, strategic planning, human resources, customer focus, had a positive and significant effect on service quality with a p-value <0,05. Primary Healthcare Centers are advised to apply accreditation standards to improve service quality, improve service systems, improve facilities and infrastructure at Primary Healthcare Center, and increase health workers' competence by participating in training. The Health Office is expected to provide post-accreditation assistance continuously.